2008
DOI: 10.1007/s00192-007-0536-0
|View full text |Cite
|
Sign up to set email alerts
|

P-Mate™, a new device allowing women to urinate in the standing position: urodynamic and satisfaction assessment

Abstract: Urodynamic parameters and satisfaction were recorded after micturition in the seated position versus the standing position with a single-use device (P-Mate) in healthy women. Healthy adult women were recruited. Eligibility criteria were: no past urological history and no urological symptoms. Volunteers were given four P-Mates to use during a week and a satisfaction questionnaire to fill. After this trial week, they were invited to perform four flowmetries, two in the seated position and two standing up, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…With auxiliary appliances, urination in the standing position is an alternative 5. In the current study, the data shows Q max does not increase with repeated episodes in the standing position, nor there was a decrease in the amount of residual urine in the bladder.…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…With auxiliary appliances, urination in the standing position is an alternative 5. In the current study, the data shows Q max does not increase with repeated episodes in the standing position, nor there was a decrease in the amount of residual urine in the bladder.…”
mentioning
confidence: 38%
“…In this study, volunteers employed homemade auxiliary appliances, made of folded art paper. There are commercialized devices available that allow women to urinate in a standing position 5. The major concern for commercialized devices is limited availability.…”
mentioning
confidence: 99%
“…As a first step toward achieving these goals, we developed a prototype squatting platform for use during urodynamic testing. Few studies have been conducted on the effects of posture during voiding on uroflow parameters in women [14,23,36,37]. Of the two studies identified that compared squatting and sitting postures during voiding, both found differences in uroflow parameters [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Voiding position can affect uroflowmetry parameters. However, several studies have indicated that voiding position has no influence on them [30][31][32].…”
Section: Flowmetry and Post-void Residual Volumementioning
confidence: 99%